Camurati–Engelmann disease-a rare cause of tetany identified on bone scintigraphy: A case report - Xie, Peng (Medicine (Baltimore), 2017)
RATIONALE: Camurati–Engelmann disease (i.e., progressive diaphyseal dysplasia) is an extremely rare autosomal dominant bone disorder. The most common clinical manifestations were chronic skeletal pain, waddling gait, muscular weakness. PATIENT CONCERNS: We described that a 27-year-old male with a 1-year history of intermittent tetany was referred for bone scintigraphy. The whole body bone scan images showed abnormal increased uptake of the tracer in the long bones of the upper and lower extremities as well as in the skull. DIAGNOSES: Combined the family history, the findings of the images and the genetic study, the diagnosis of Camurati–Engelmann disease was confirmed. INTERVENTIONS AND OUTCOMES: The patient responded well to the treatment of calcium gluconate. LESSONS: Bone scintigraphy would be helpful in the diagnosis and assessing the severity of Camurati–Engelmann disease.